Growth hormone attenuates skeletal muscle changes in experimental chronic heart failure - dos Santos, Denis Pioli [UNESP]; Okoshi, Katashi [UNESP]; Moreira, Vanessa O. [UNESP]; Seiva, Fabio R. F. [UNESP]; Alves de Almeida, Fernanda Losi [UNESP]; Padovani, Carlos Roberto [UNESP]; Carvalho, Robson Francisco [UNESP]; Okoshi, Marina Politi [UNESP]; Cicogna, Antonio Carlos [UNESP]; Barros Castro, Ana Valeria [UNESP]; Dal Pai-Silva, Maeli [UNESP] (Churchill Livingstone, 2010)
Objective: This study evaluated the effects of growth hormone (GH) on morphology and myogenic regulatory factors (MRF) gene expression in skeletal muscle of rats with ascending aortic stenosis (AAS) induced chronic heart failure.Design: Male 90-100 g Wistar rats were subjected to thoracotomy. AAS was created by placing a stainless-steel clip on the ascending aorta. Twenty five weeks after surgery, rats were treated with daily subcutaneous injections of recombinant human GH (2 mg/kg/day; AAS-GH group) or saline (AAS group) for 14 days. Sham-operated animals served as controls. Left ventricular (LV) function was assessed before and after treatment. IGF-1 serum levels were measured by ELISA. After anesthesia, soleus muscle was frozen in liquid nitrogen. Histological sections were stained with HE and picrosirius red to calculate muscle fiber cross-sectional area and collagen fractional area, respectively. MRF myogenin and MyoD expression was analyzed by reverse transcription PCR.Results: Body weight was similar between groups. AAS and AAS-GH groups presented dilated left atrium, left ventricular (LV) hypertrophy (LV mass index: Control 1.90 +/- 0.15; AAS 3.11 +/- 0.44; AAS-GH 2.94 +/- 0.47 g/kg; p < 0.05 AAS and AAS-GH vs. Control), and reduced LV posterior wall shortening velocity. Soleus muscle fiber area was significantly lower in AAS than in Control and AAS-GH groups; there was no difference between AAS-GH and Control groups. Collagen fractional area was significantly higher in MS than Control; AAS-GH did not differ from both Control and AAS groups. Serum IGF-1 levels decreased in AAS compared to Control. MyoD mRNA was significantly higher in AAS-GH than AAS; there was no difference between AAS-GH and Control groups. Myogenin mRNA levels were similar between groups.Conclusion: In rats with aortic stenosis-induced heart failure, growth hormone administration increases MyoD gene expression above non-treated animal levels, preserves muscular trophism and attenuates interstitial fibrosis. These results suggest that growth hormone may have a potential role as an adjuvant therapy for chronic heart failure. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Heart failure; Growth hormone; Skeletal muscle; Myogenic regulatory factors; Aortic stenosis; Rats; Muscle atrophy